Reduction of Mercury(II) by the carbon dioxide radical anion: a theoretical and experimental investigation - Berkovic, Andrea Mariela (2010)
The laser flash photolysis technique (λexc = 266 nm) was used to investigate the mechanism of the HgCl2 reduction mediated by CO2·− radicals in the temperature range 291.7−308.0 K. For this purpose, the CO2·− radicals were generated by scavenging of sulfate radicals by formic acid. The absorbance of the reduced radical of methyl viologen, a competitive scavenger of CO2·−, was monitored at 390 nm. Moreover, theoretical calculations, including solvent effects, were also performed within the framework of the density functional theory for various chemical species of Hg(I) and Hg(II) to aid in the modeling of the reaction of reduction of HgCl2 by CO2·−.